Advanced Nationalist Political Activity in Ireland 1910-1917 - Brown, Peter (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2023)
This thesis examines the political, as opposed to military, activities of advanced nationalists in Ireland, including the Irish Volunteers, the Irish Republican Brotherhood, Sinn Fein, the labour movement, the women's movement, and advanced men and women in the Gaelic League, from the 1910 elections to the 1917 Sinn Fein Ard Fheis. It finds that, even before 1917, Sinn Fein did not advocate a 'dual monarchy'; it was simply accused of doing so by a small number of militants because its constitution was framed so as to be inclusive of non-republicans. Thus, the IRB and Sinn Fein were able to work in harmony during this period, with even that militant group - who would go on to gain control of the IRB Supreme Council - becoming reconciled after a bitter controversy that lasted for most of 1910. Sinn Fein, the IRB, labour and the nationalist women worked successfully together to prevent an address of welcome to King George V when he visited Dublin in 1911, even drawing in - albeit somewhat grudgingly - members of the United Irish League and the Ancient Order of Hibernians. Both Sinn Fein and the editors of the IRB paper Irish Freedom were fully involved in the debate around the Third Home Rule Bill, despite not being in favour of home rule as a final settlement. Advanced members of the Gaelic League, together with members of the IRB and Sinn Fein, were behind the formation of the Irish Volunteers in 1913. They recruited members of the UIL and AOH onto the Provisional Committee, but the Volunteer manifesto pointedly omitted any mention of home rule, and the committee strongly resisted any attempt by the Irish Parliamentary Party to control the movement, eventually being forced to add 25 members nominated by the IPP, but expelling them again in September 1914. Organisers of the much reduced Irish Volunteers were active in the opposition to recruiting to the British Army during the First World War, a political activity that was traditionally associated with Sinn Fein. Following the Easter Rising of 1916, new organisations sprang up; none of these described themselves as republican, and all were absorbed into Sinn Fein. Although Sinn Fein, at the 1917 Ard Fheis, was formally constituted as a republican political party, it is seen that election literature both before and after the Ard Fheis made little mention of a republic. It is argued that for most people at that time, 'republic' was no more than a synonym for 'independence'.
APPROVED
Keywords: Arthur Griffith; Bulmer Hobson; P.S. O'Hegarty; Eoin MacNeill; Royal visit 1911; Anti-recruitment; Third Home Rule Bill; Easter Rising; 1917 Ard Fheis; Republic; Irish Republic; Sinn Fein; Dual monarchy; Irish Republican Brotherhood; IRB; Advanced nationalists; Gaelic League; Irish Volunteers; Revolutionary period; Irish Freedom